Functional regulation of vascular and platelet activity during thrombosis by nitric oxide and endothelial nitric oxide synthase - Moore, Christopher; Tymvios, Charalambos; Michael, Emerson (Thrombosis and Haemostasis, 2010)
Nitric oxide (NO) regulates both vascular tone and platelet function. Since thrombotic diseases and their animal models consist of both vascular and platelet components, the functional mechanisms by which NO and endothelial nitric oxide synthase (eNOS) regulate thrombotic events are unclear. Experiments were conducted by measuring collagen-induced aggregation of freely circulating radio-labelled platelets in the pulmonary vasculature of anaesthetised mice via external detection probes. In addition, cardiac haemodynamic function was assessed by invasive catheterisation during thrombotic stimulation. Platelet aggregation responses were shown to occur independently of changes in vessel tone induced by pharmacological vasoconstriction or vasodilatation. Acute NOS inhibition significantly potentiated the amplitude and duration of platelet aggregation and an NO donor had an inhibitory effect. In contrast, in eNOS−/− mice, the amplitude of platelet aggregation was not affected although the response was protracted following moderate thrombotic stimulation. Thrombosis induced changes in haemodynamic performance were sensitive to vasomodulation and were potentiated by both NOS inhibition and in eNOS−/− mice. In conclusion, endogenous NO and exogenously applied NO donors exert an antithrombotic effect in vivo through a direct suppression of platelet aggregation. In contrast, eNOS exerts a powerful antithrombotic effect upon the vascular components of thrombosis but has a more subtle effect on the duration of thrombotic responses that are platelet-mediated. Our data demonstrate the differential roles of eNOS and general NO bioavailability in regulating vascular and platelet activity during thrombosis.
Keywords: Animal models; endothelium; nitric oxide; pharmacology; platelet